Post-operative periprosthetic humeral fractures after reverse shoulder arthroplasty: a review of the literature - Canton, Gianluca; Fazzari, Francesco; Fattori, Roberto; Ratti, Chiara; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Post-operative periprosthetic shoulder fractures incidence is gradually raising due to aging of population and increasing of reverse total shoulder arthroplasty (RTSA). Management of this complication represents a challenge for the orthopedic surgeon. Aim of the present study is to critically review the recent literature about epidemiology, risk factors, diagnosis, management and outcome of post-operative periprosthetic humeral  fractures occurring on RTSA. Methods: A systematic search of Embase, Medline and Pubmed was performed by two reviewers who selected the eligible papers favoring studies published in the last ten years. Epidemiology, risk factors, diagnostic features, clinical management and outcome of different techniques were all reviewed. Results: 31 studies including reviews, meta-analysis, case reports, clinical and biomechanical studies were selected. Conclusions: Correct clinical management requires adequate diagnosis and evaluation of risk factors. Conservative treatment is rarely indicated. Locking plate fixation and revision arthroplasty are both valuable treatment methods. Surgical technique should be chosen considering age and functional demand, comorbidities, fracture morphology and location, bone quality and stability of the implant. Given the correct indication all surgical treatment can lead to satisfactory clinical and radiographic results despite a relevant complication rate.